2005
DOI: 10.5194/angeo-23-3439-2005
|View full text |Cite
|
Sign up to set email alerts
|

Transition region of TEC enhancement phenomena during geomagnetically disturbed periods at mid-latitudes

Abstract: Abstract. Large-scale TEC perturbations/enhancements observed during the day sectors of major storm periods, 12-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Various studies suggested that the ionospheric electron content perturbations were also caused by the penetration of magnetospheric electric fields, which were controlled or modulated by the oscillations in the IMF/solar wind pressure (Borovsky, et al, 1993;Fejer and Scherliess, 1998;Sobral et al, 1997;Huang et al, 2002;Unnikrishnan, et al, 2005). The energy and particle injection that takes place during magnetospheric disturbances produce multiple changes to the Earth's high latitude ionosphere-thermosphere system (Pincheira et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies suggested that the ionospheric electron content perturbations were also caused by the penetration of magnetospheric electric fields, which were controlled or modulated by the oscillations in the IMF/solar wind pressure (Borovsky, et al, 1993;Fejer and Scherliess, 1998;Sobral et al, 1997;Huang et al, 2002;Unnikrishnan, et al, 2005). The energy and particle injection that takes place during magnetospheric disturbances produce multiple changes to the Earth's high latitude ionosphere-thermosphere system (Pincheira et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is suggested that, the nighttime TIDs play an important role to generate the 3‐m‐scale irregularity in the mid latitude F region ionosphere [ Saito et al , 2002]. Also, the TEC perturbations observed on storm days exhibit interesting transitions characterized by decreasing magnitude of perturbation component, at the region 39°–34°N (30°–25°N geomagnetically), due to the interaction with higher background content of expanded anomaly crest [ Unnikrishnan et al , 2005].…”
Section: Comparison Of Nonlinear Aspects Of Ionosphere Under Various mentioning
confidence: 99%
“…The storm‐associated disturbance electric field, which is active at equatorial/low latitudes, the associated poleward expansion of equatorial ionization anomaly (EIA), and the storm‐driven disturbance neutral wind system originating at the high‐latitude regime will produce unpredictable TEC perturbations over the midlatitude region. TEC perturbations propagating through this region suffer severe damping and undergo interesting transitions due to the ionization gradients of expanded anomaly crest [ Unnikrishnan et al , 2005]. Hence the latitude sector of the present study, 32–44°N, and the five locations, i.e., 32.1, 35.1, 38.1, 41.1, and 44.1°N, are very sensitive to ionospheric disturbances and irregularities, and nonlinear analysis may reveal more about the underlying dynamics.…”
Section: Comparison Of Nonlinear and Chaotic Aspects Of Daytime And Nmentioning
confidence: 99%